Comparison of BIRADS lexicon to breast biopsy findings in low resource countries - Prabhala, Shailaja; Srirambhatla, Annapurna; Pasula, Sujatha (ScienceRise: Medical Science, 2022)
Breast cancer is the most common malignancy in women worldwide and early detection is of utmost importance. In developed countries, mandatory mammographic screening programs help in early detection, whereas, in developing countries cancer is often detected at an advanced stage. The BIRADS guidelines permit a standard approach and follow up for breast lesions. Many newer imaging modalities are being available for better diagnosis. Breast lesions have a varied spectrum and the gold standard for diagnosis of breast cancer is based on histopathological examination of tissue. At times, even on trucut biopsy, it is difficult to categorize the lesion as the tissue studied is limited and some evolving lesions may have overlapping features. As there are limitations to both radiologic and pathologic approaches, the general and accepted way is to combine both modalities to arrive at a diagnosis. The aim: The aim of the study was to find out how well the BIRADS radiological findings correlate with histopathological findings on breast biopsies. Materials and methods: A MEDLINE search for articles published in English language, with key words as breast biopsy histopathology and BIRADS was done for the years between 1985 and 2021. In addition, other cross-referenced articles were also searched for relevant data. Results: There is good correlation between BIRADS category 1, 2 and 5 with the findings on core needle biopsy in breast lumps i.e., good correlation is seen at the end of spectrum of breast lesions in totally benign and unequivocally malignant lesions. But this correlation is lacking in the middle of the spectrum i.e., in borderline/intermediate category of BIRADS. Conclusion: The non-suspicious (BIRADS 1/ 2) and highly suspicious (BIRADS 4C/5) compare very well with the histopathologic findings. It is the grey zone i.e., BIRADS 3/4A which has a wide and variable predictive value for breast cancer when compared with histopathology and imaging study alone is insufficient and mandates histopathology in all such cases